2004
DOI: 10.1016/j.chembiol.2004.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Mediated Transcription Elongation Control Using Triplex-Based Padlock Oligonucleotides

Abstract: Triplex-forming oligonucleotides (TFOs) provide useful tools for the artificial regulation of gene expression at the transcriptional level. They can become topologically linked to their DNA target upon circularization, thereby forming very stable triple helical structures. These "padlock oligonucleotides" are able to interfere with transcription elongation when their target site is located in the transcribed region of a gene. In vitro transcription experiments showed that a bacterial RNA polymerase was stopped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 41 publications
(5 reference statements)
0
10
0
Order By: Relevance
“…2). The first type contains G and T in the loop of the TFO and can form a triple helix in the presence of the triplex‐stabilizing agent 6‐[3‐(dimethylamino)propyl]amino‐11‐methoxy‐benzo[f]quino‐[3,4‐b]quinoxaline (BQQ), as already described in our previous work [10–14]. The second one can form a triple helix at acidic pH.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…2). The first type contains G and T in the loop of the TFO and can form a triple helix in the presence of the triplex‐stabilizing agent 6‐[3‐(dimethylamino)propyl]amino‐11‐methoxy‐benzo[f]quino‐[3,4‐b]quinoxaline (BQQ), as already described in our previous work [10–14]. The second one can form a triple helix at acidic pH.…”
Section: Resultsmentioning
confidence: 91%
“…We have shown that the stability of the triple helix made by the topologically linked TFO, also called padlock oligonucleotide, was enhanced compared to that formed with a linear TFO [10]. For example, we showed that such a padlock oligonucleotide strongly inhibits DNA digestion by a restriction endonuclease, and that the complex is strong enough to inhibit the elongation of transcription by an RNA polymerase [11]. The triple helix used in these studies involved a third strand containing G and T, binding of which was stabilized by the use of a triplex specific intercalator.…”
mentioning
confidence: 99%
“…9). In the absence of BQQ, the circular oligonucleotide was free to move from its binding site, whereas addition of BQQ locked the oligonucleotide around its target, resulting in inhibition of cleavage by a restriction enzyme [143] and blockage of transcription elongation by an RNA polymerase [144]. This approach could lead to new strategies aimed at regulating gene expression by small molecules.…”
Section: Stabilization Of Intermolecular Triple Helicesmentioning
confidence: 99%
“…We chose another plasmid, pRLCMV (4079 bp), on which another oligopurine sequence, 5'-GAAGAAGGAGAAAAAA-3', provides a target for TFO2. [12] The sequences of the two 5'-phosphorylated oligonucleotides are shown in Figure 1. The design of the TFOs resembles the one described in some of our previous work.…”
mentioning
confidence: 99%
“…[10] The circularized oligonucleotide might remain locked on its target sequence or slide on the DNA double-helix depending on whether conditions favor triple-helix formation or not. [11,12] The so-called padlock oligonucleotides for double-stranded DNA might have several applications, including plasmid targeting [13] and sequence-specific labeling of DNA for observation by electron, atomic force, or optical microscopy. [14,15] Here, we report the preparation and characterization of a novel supramolecular plasmid DNA construct containing two different plasmid molecules that are linked by a circular oligonucleotide.…”
mentioning
confidence: 99%